Excellent Service Management in Islamic Boarding Schools: A SERVQUAL Analysis of Educational Service Quality - Ninik Sugiyarti; Sopidi Sopidi; Iis Arifudin; Ria Yulia Gloria (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
This study aims to analyze the implementation of excellent service management at Al Mu’minien Modern Islamic Boarding School in Indramayu, identify supporting and inhibiting factors, and explore strategies to improve the quality of educational services in Islamic educational institutions. This research employed a qualitative field research approach with a descriptive analytical design. Data were collected through semi-structured interviews, documentation, and literature review. The main informant of this study was the pesantren operator responsible for administrative services and student data management. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing, while data triangulation was applied to ensure the credibility of the findings. The results show that the implementation of service management in the pesantren reflects the five dimensions of the SERVQUAL model: tangibles, reliability, responsiveness, assurance, and empathy. These dimensions are manifested in the availability of adequate facilities, structured educational programs, responsive communication with parents, transparent financial management, and personal guidance for students. The study also identifies several challenges related to limited digital infrastructure, variations in human resource competencies, and financial constraints. These findings indicate that improving service quality plays an important role in strengthening institutional credibility and increasing public trust in Islamic educational institutions.